Can Regulations Make It More Difficult to Serve the Poor? : The Case of Childcare Services in istanbul, Turkey - Aran, Meltem A.; Aktakke, Nazli; Munoz Boudet, Ana Maria (Taylor and Francis, 2016)
Private and community-driven efforts can be an important resource to expand early childhood education and care (ECEC) services to poor children, under the right conditions and design. The regulations imposed on private ECEC provision, while having an impact on quality, may increase costs of provision and in return prices of services, reducing accessibility and affordability for poor households. This paper considers the impact of regulations on private ECEC in a highly regulated childcare market in a developing country. Using data from a recently fielded survey that sampled 141 private ECEC facilities in Istanbul, Turkey, the paper looks at the impact of fixed regulations on prices and poor children’s access to services, in particular the outdoor space requirement that was originally imposed on private providers in the 1960s and has over time become more difficult to fulfill in densely populated districts of the city. The paper estimates that controlling for other provider characteristics, in districts where such requirement is more binding, the price of childcare services increases by 376.2 TL per child per month and the percentage of children enrolled coming from poor backgrounds lowers by 15.1% points than in districts where such standard proves less challenging.